Persepsi Guru PAI Tentang Pelaksanaan Supervisi oleh Kepala Sekolah Hubungannya dengan Kreativitas Guru dalam Mengajar: (Penelitian Guru PAI di SMP Se-Kecamatan Cileunyi Kabupaten Bandung) - helmi aziz (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2019)
This study aims to determine: (1) the reality of the perceptions of Islamic Education teachers (PAI) on the role of supervisors as supervisors, (2) to know the reality of their creativity in teaching, and (3) to find out the relationship between the two. The method used in this study is a quantitative analysis based on inferencing statistical models. The data collection is done using observation techniques, interviews, and questionnaires. After the data is collected, it is then processed using logic analysis for qualitative and statistical analysis for quantitative data using descriptive statistics, regression, and correlation. Based on the hypothesis test, the perception of PAI teachers about the implementation of supervision by the principal contributed positively and significantly to the teacher's creativity in teaching. Based on this, it can be concluded that in order for teacher creativity to increase in learning, the competency of the principal as a supervisor should be optimized so as to be able to carry out the leadership functions in accordance with the field of work. In addition, the implementation of administrative supervision and learning activities needs to be carried out formally or incidentally, so that the teacher's creativity in teaching increases